Penggunaan Smart Card dan Database dalam Aplikasi E-KTM Multifungsi - Purnama, Heru Djulianto; Prijono, Agus (Zenit, 2014)
Most of the student identification cards (KTM) are not used optimally, and many of them are only used for identification. In fact, KTM is a smart card which has several advantages over barcode card. A smart card has a unique id number that cannot be duplicated since the process of identification makes use of radio frequency. In addition, the smart card has EEPROM, which can perform the function of storing data. In this research, it is realized in the form of simulations and prototype system of E-KTM, which use smart card-based database applications that will be applied to the library, food court, parking access, and room access. Based on the test results, the E-KTM multifunction systems have been successfully realized in the form of simulations and prototypes for both software and hardware.Keywords : smart cards, systems, databases, E-KTM